As atitudes e comportamentos decorrentes da acção das campanhas de desnutrição em crianças realizadas pela ONG SD junto da população do distrito de Monapo – Nampula - Pereira, Neusa da Silva; Brandao, Nuno Goulart (E-Acadêmica, 2022)
In Mozambique 43% of children aged between 0 and 5 years old suffer from chronic malnutrition. Problems related to nutritional status are more prevalent in rural areas of the country, especially in the north, with greater emphasis on the provinces of Nampula and Cabo Delgado. In the various prevention and resolution measures, the communication tools, their strategies and actions can contribute to the information, awareness and awareness of the populations. The study presented here is the result of a doctoral investigation focusing on the effectiveness of social marketing campaigns to reduce malnutrition rates in children in the Monapo district, proposed by a non-governmental organization, which for ethical and protection reasons, the fictitious name SD was used. In this way, the main objective is based on understanding the attitudes and behaviors of pregnant mothers and mothers of children from 0 to 5 years of age in relation to the nutrition campaign. Thus, from a qualitative methodological approach perspective, in the context of the interpretive paradigm, the main results of the present investigation reveal a strong awareness of mothers about the risks associated with the problem, the benefits present in the ideal behavior and also in the face of a clear will to follow in accordance in the face of behavior. However, contextual and environmental issues proved to be a major obstacle to the practical applicability of these behaviors.